Numerical Simulation of Heat Transfer from PV Panel with a Wetted Porous Wick - Abed, Angham Fadil; Hachim, Dhafeer Manee; Najim, Saleh E. (Basrah Journal for Engineering Sciences, 2021)
The panel absorbed solar radiation and majority of this radiation is transform into a heat, and it is usually wasted and useless. At higher cell temperature, the current out of the cell has an unnoticeable rise, but the voltage value will drop significantly, resulting in a reduction in maximum power produced. The cooling method is therefore beneficial to keep the panel at the operation temperature. A simulation model is developed using COMSOL Multiphysics software version 3.5 software to investigate the enhancement in performance of a PV water cooling module (PVW module) based on a passive and simple cooling technique using a wetted cotton porous wick attached on the PV panel’s back side and compare with uncooled PV panel (PVREF module). Unsteady, laminar and 2-D, the flow in the proposed modules is assumed. The input parameters were taken from a real weather condition was perform in Najaf-Iraq. The effect of variation of mass flow rate is also studied in the present work. Good agreement was obtained for PVREF module with previously researches.